Computational Seismic Analysis of Dry-Stack Block Masonry Wall - Irfan Khan; Akhtar Gul; Khan Shahzada; Nisar Ali Khan; Faisal Ur Rehman; Qazi Samiullah; Muhammad Arsalan Khattak (Salehan Institute of Higher Education, 2021)
In this research the computational modeling of Dry-Stack Block Masonry (DSM) walls subjected to cyclic monotonic loading testing is done. The analytical results were compared with experimental test results of the unreinforced and unconfined DSM cantilever walls subjected to lateral loading along with a constant axial load. ABAQUS has been used for Finite Element Modeling and analysis of the wall. Various material properties are defined for the wall in the software and modeled as a homogeneous material. The proposed numerical models had a good correlation with the experimental data. The test results discussion includes failure moods, load displacement curves, and stress/strain profile. Doi: 10.28991/cej-2021-03091668 Full Text: PDF